High-purity preparation of HSV-2 vaccine candidate ACAM529 is immunogenic and efficacious in vivo. - Sophia T Mundle (Public Library of Science (PLoS), 2013)
Genital herpes is a sexually transmitted infection (STI) caused by herpes simplex virus 2 (HSV-2) and to a lesser extent herpes simplex virus 1 (HSV-1). Infection by HSV-2 is life-long and is associated with significant cost to healthcare systems and social stigma despite the highly prevalent nature of the disease. For instance, the proportion of HSV-2 seropositive to seronegative adults is approximately 1 in 5 in the US and greater than 4 in 5 in some areas of sub-Saharan Africa. The replication-defective vaccine strain virus dl5-29 was re-derived using cells appropriate for GMP manufacturing and renamed ACAM529. Immunization with dl5-29 was previously reported to be protective both in mice and in guinea pigs, however these studies were performed with vaccine that was purified using methods that cannot be scaled for manufacturing of clinical material. Here we describe methods which serve as a major step towards preparation of ACAM529 which may be suitable for testing in humans. ACAM529 can be harvested from infected cell culture of the trans-complementing cell line AV529 clone 19 (AV529-19) without mechanical cell disruption. ACAM529 may then be purified with respect to host cell DNA and proteins by a novel purification scheme, which includes a combination of endonuclease treatment, depth filtration, anion-exchange chromatography and ultrafiltration/diafiltration (UF/DF). The resultant virus retains infectivity and is ∼ 200-fold more pure with respect to host cell DNA and proteins than is ACAM529 purified by ultracentrifugation. Additionally, we describe a side-by-side comparison of chromatography-purified ACAM529 with sucrose cushion-purified ACAM529, which shows that both preparations are equally immunogenic and protective when tested in vivo.